Development of Science Learning Modules with Differentiated Approach Assisted by AI Canva Human Digestive System Material to Improve Learning Outcomes - Yuliani, Yuliani; Kusrina, Tity; Suriswo, Suriswo (Journal of English Language and Education, 2025)
Science education in elementary school is essential for developing students' critical thinking and understanding of natural processes. This study aims to develop and evaluate a differentiated science learning module assisted by AI Canva on the human digestive system to improve fifth-grade students' learning outcomes in Tegal Regency. Using the ADDIE development model, this Research and Development (RD) study collected data through questionnaires, interviews, observations, and documentation. The sample consisted of two fifth-grade classes: a control group and an experimental group. Data were analyzed using normality, homogeneity, t-tests, and feasibility assessments. The results show that the module is highly feasible, with material validation at 86.53% and media validation at 94.13%. Student learning outcomes in the experimental class increased from 81.66% (pre-test) to 100% (post-test), indicating the module's significant effectiveness. In conclusion, the AI Canva-assisted differentiated module is both feasible and effective in enhancing students’ understanding of the human digestive system.